Gene expansion and retention leads to a diverse tyrosine kinase superfamily in amphioxus - D'Aniello, Salvatore; Irimia, Manuel; Maeso, Ignacio; Pascual-Anaya, Juan; Jiménez-Delgado, Senda; Bertrand, Stephanie; Garcia-Fernàndez, Jordi (Oxford University Press, 2008)
Tyrosine kinase (TK) proteins play a central role in cellular behavior and development of animals. The expansion of this superfamily is regarded as a key event in the evolution of the complex signaling pathways and gene networks of metazoans and is a prominent example of how shuffling of protein modules may generate molecular novelties. Using the intron/exon structure within the TK domain (TK intron code) as a complementary tool for the assignment of orthology and paralogy, we identified and studied the 118 TK proteins of the amphioxus Branchiostoma floridae genome to elucidate TK gene family evolution in metazoans and chordates in particular. Unlike all characterized metazoans to date, amphioxus has members of all known widespread TK families, with not a single loss. Putting amphioxus TKs in an evolutionary context, including new data from the cnidarian Nematostella vectensis, the echinoderm Strongylocentrotus purpuratus, and the ascidian Ciona intestinalis, we suggest new evolutionary histories for different TK families and draw a new global picture of gene loss/gain in the different phyla. Surprisingly, our survey also detected an unprecedented expansion of a group of closely related TK families, including TIE, FGFR, PDGFR, and RET, due most probably to massive gene duplication and exon shuffling. Based on their highly similar intron/exon structure at the TK domain, we suggest that this group of TK families constitute a superfamily of TK proteins, which we termed EXpanding TK, after their seemingly unique propensity to gene duplication and exon shuffling, not only in amphioxus but also across all metazoan groups. Due to this extreme tendency to both retention and expansion of TK genes, amphioxus harbors the richest and most diverse TK repertoire among all metazoans studied so far, retaining most of the gene complement of its ancestors, but having evolved its own repertoire of genetic novelties.
Keywords: Genética evolutiva; Amphioxus; Tyrosine kinase; Genome evolution; Gene expansion